The Impact of Teaching History through Imaginative Learning Strategy on Developing Historical Thinking among Tenth Graders in Jordan - Rawadieh, Saleh Moh'd; Karim , Ali Faraj Rajab (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the impact of teaching history through the imaginative learning strategy in the development of historical thinking among the 10th grade students in Jordan. To achieve the objectives of the study, the semi-experimental approach was used. The study sample consisted of (60) students who were randomly distributed into two sections randomly selected from 10th grade students in Khalid Bin Al Walid High School: the experimental group, which consisted of 30 students who were taught through the imaginative learning strategy and the control group, which consisted of 30 students who were taught through the regular method. The historical thinking scale was developed as an instrument to collect data from the study sample. In addition, the researchers used the third unit of the history textbook of the loth grade which entitled: "the contemporary history of Jordan" The findings showed that there were statistically significant differences among the post scores of the two groups on the total historical thinking scale according to fields and they were in favor of the experimental group that adopted the imaginative learning strategy. According to the results of the study, the researchers recommended the need for using the imaginative learning strategy in teaching history to develop the historical thinking skills among students.